Penerapan Bahasa Jurnalistik pada Majalah Islam: Studi Kasus Majalah Hidayatullah - Utami, Dhita Putri (Universitas Ibn Khaldun Bogor, 2020)
This study aims to determine: 1) News search process at Hidayatullah Magazine 2) Discussing the application of journalism language to the Hidayatullah Magazine, a spesial report section on the 9th and 11th edition of 2019. The approach used is qualitative with the method of content analysis in the special report section of the Hidayatullah Magazine,data sources used in this study are primary data, which includes observation interview in Hidayatullah Magazine 9th and 11th edition 2019 and secondary data which includes references to journal, books and other writings relating to this research. The result of this study indicate that the news search process in Hidayatullah Magazine has met the criteria for the news search process in general, namely a literature review of observations and interviews as well as the application of the language of journalism to the Hidayatullah Magazine not yet fully in accordance with the simple characteristics of a short interasting that is clearly democratic and populist. From the result of analysis found 17 data that are not in accordance with these characteristics errors occur in the theme of the word kayan which is excessive use of words that are not simple mistakes in writing words and not clearly difficult for some people to understand.AbstrakPenelitian ini bertujuan untuk mengetahui: 1) Proses pencarian berita pada Majalah Hidayatullah 2) Membahas tentang penerapan bahasa jurnalistik pada Majalah Hidayatullah rubrik khusus edisi 9 dan 11 tahun 2019. Pendekatan yang digunakan adalah kualitatif dengan metode isi. analisis pada bagian laporan khusus Majalah Hidayatullah, sumber data yang digunakan dalam penelitian ini adalah data primer, yang meliputi wawancara observasi di Majalah Hidayatullah edisi 9 dan 11 tahun 2019 dan data sekunder yang meliputi referensi jurnal, buku dan tulisan lain yang berkaitan dengan penelitian ini. Hasil penelitian ini menunjukkan bahwa proses pencarian berita di Majalah Hidayatullah sudah memenuhi kriteria proses pencarian berita secara umum yaitu tinjauan pustaka observasi dan wawancara serta penerapan bahasa jurnalistik pada Majalah Hidayatullah belum sepenuhnya sesuai dengan ciri-ciri sederhana dari interasting pendek yang jelas demokratis dan kerakyatan. Dari hasil analisis ditemukan 17 data yang tidak sesuai dengan ciri-ciri tersebut terjadi kesalahan pada tema kata kayan yaitu penggunaan kata yang berlebihan yang tidak sederhana kesalahan dalam penulisan kata dan tidak jelas sulit dipahami oleh sebagian orang.